Female crack cocaine users under treatment at therapeutic communities in southern Brazil: characteristics, pattern of consumption, and psychiatric comorbidities - Hess,Adriana Raquel Binsfeld (2019)
Abstract Objective To explore and describe sociodemographic characteristics, crack consumption patterns, and psychiatric comorbidities of female crack users receiving treatment at therapeutic communities. Methods This was a cross-sectional, descriptive, quantitative study. Forty-six women who abstained from crack use were assessed using a sociodemographic questionnaire, the Mini-Mental State Examination (MMSE), the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), and a profile of crack use questionnaire. Descriptive statistical analyses were conducted. Results Participants had a mean age of 31.02 years (standard deviation [SD] = 7.73), most were single (76.1%), white (67.4%) and had complete or incomplete elementary education (43.5%). Before treatment, 65.2% of the women reported using crack every day; 46.3% smoked between 10 to 30 crack rocks per week. Mean treatment time was 63.56 days (SD = 75.85), with a mean of 80.41 days of abstinence (SD = 74.52) and 3.37 previous treatments (SD = 5.49). Mean age upon crack use initiation was 22.61 years (SD = 8.06), and the most frequent motivation to start using crack was curiosity (78.3%). The mean lifetime duration of crack use was 82.26 months (SD = 74.76), and the physical complications most frequently reported were weight loss (93.5%), followed by sleep problems (87%). In this study, the most prevalent psychiatric diagnoses were major depressive episode (60.87%), followed by post-traumatic stress disorder (52.17%) and generalized anxiety disorder (13.07%). Conclusions Overall, a pattern of high consumption of crack was observed. The results show a high frequency of mood and anxiety disorders, with the highest frequencies found for major depressive episode and post-traumatic stress disorder.